2018
DOI: 10.3390/en11102833
|View full text |Cite
|
Sign up to set email alerts
|

Co-Optimization of Energy and Reserve Capacity Considering Renewable Energy Unit with Uncertainty

Abstract: This paper proposes a system model for optimal dispatch of the energy and reserve capacity considering uncertain load demand and unsteady power generation. This implicates uncertainty in managing the power demand along with the consideration of utility, user and environmental objectives. The model takes into consideration a day-ahead electricity market that involves the varying power demand bids and generates a required amount of energy in addition with reserve capacity. The lost opportunity cost is also consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…The recent literature has provided enough directions to make the system more reliable, we have combined all of the major concepts proposed individually in the cited papers i.e, load forecasting to dispatch of generation along with reserve using a heuristic algorithm, incorporation of uncertain RES to the provision of a spinning reserve through BSS. Furthermore, the discussion and analysis in this paper extend the preliminary results in our earlier paper [31] in various aspects. First, here we have implemented the load forecasting technique instead of taking arbitrary load demand.…”
Section: Motivation and Background Literaturesupporting
confidence: 84%
See 2 more Smart Citations
“…The recent literature has provided enough directions to make the system more reliable, we have combined all of the major concepts proposed individually in the cited papers i.e, load forecasting to dispatch of generation along with reserve using a heuristic algorithm, incorporation of uncertain RES to the provision of a spinning reserve through BSS. Furthermore, the discussion and analysis in this paper extend the preliminary results in our earlier paper [31] in various aspects. First, here we have implemented the load forecasting technique instead of taking arbitrary load demand.…”
Section: Motivation and Background Literaturesupporting
confidence: 84%
“…Therefore, in this regard some studies have quantified the provision of reserve energy as given in [25]- [30]. These studies have focused solely on optimizing the economic operation of the combined dispatch of energy and reserve [31].…”
Section: Motivation and Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The study did not, however, use a grid model where the power flow is a function of voltage angle difference between the two nodes. Another study [24] presented a joint energy and reserve model that did not include energy storage systems (ESS) and demand response (DR) as well as aggregated all technologies in one node. Joint energy and reserve model was presented in [25] where authors observed the influence of electric vehicle (EV) fleet on the system operation.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [2][3][4][5][6] establishes an optimization model aiming at maximizing the profit of the system. Reference [7][8][9][10][11] synthetically considers the operation cost and emission cost of microgrid, and establishes a multi-objective optimization model to minimize the economic cost and emission of microgrid. Reference [12] analyzed the characteristics of distributed generation and the mathematical model of optimization objectives in detail, and proposed a multi-objective immune algorithm of niche evolution for the optimal management of distributed power output in microgrid.…”
Section: Introductionmentioning
confidence: 99%